Impediments in promoting communicative competence among students of English as a Second Language (With special reference to undergraduates of the University of Jaffna) - Suntharesan, V. (Ph.D. in Linguistics, 2012)
There has been a greater focus on English language teaching in recent times in this country, because of the global status of English, and people all over the world are keenly learning it. Communicative Language Teaching (CLT) methodology has been implemented in many contexts of ESL teaching. However, in many South Asian countries including Sri Lanka, the implementation of CLT methodology encounters many problems as CLT clashes with the native cultural environment of learning and certain other factors. This study is intended to discover the impediments of students at tertiary level developing their communicative competence, with special reference to the ESL (English as a Second Language) students of the University of Jaffna, Sri Lanka. The methodology adopted in the research is qualitative. Questionnaire and informal discussion were used as instruments of data collection. The data revealed the presence of a positive attitude toward English among most of the students and a severe lack of exposure to this language at home, in the university, and in social surroundings. Subsequently, certain demotivating factors, which hinder the practice of CLT in classes are identified and recommendations are made to provide maximum exposure to students with the aim of promoting their communicative competence. These demotivating factors include inadequate vocabulary, structure difficulties, spelling errors, and listening difficulties of students, plus the infrequent use of technology and Tamil in English as a second language classes.